Relationship between blood lactate and excess CO2 in elite cyclists - Anderson, G. S.; Rhodes, E. C. (Journal of Sports Sciences, 1991)
The studies on blood lactate and excess CO2 in elite cyclists led to the following implications: - OBLA levels vary greatly between individuals and should only be interpreted on an intra-individual basis, and - non-invasive estimates of OBLA are particularly suspect.